HPS6 Regulates the Biogenesis of Weibel–Palade Body in Endothelial Cells Through Trafficking v-ATPase to Its Limiting Membrane - Lu, Jiran; Ma, Jing; Hao, Zhenhua; Li, Wei (Frontiers in Cell and Developmental Biology, 2022)
The Weibel–Palade body (WPB) is one of the lysosome-related organelles (LROs) in endothelial cells, whose main content is von Willebrand factor (vWF). The biogenesis of LROs is regulated by the Hermansky–Pudlak syndrome (HPS) protein-associated complexes through transporting cargo proteins to WPBs. Our previous studies have shown that HPS6, a subunit of BLOC-2 complex, is likely involved in the maturation of WPBs. However, the underlying mechanism remains unknown. In this study, we found that the knockdown of HPS6 in human umbilical vein endothelial cells (HUVECs) resulted in misshaped WPBs, decreased WPB number, and impaired vWF tubulation, which are similar to the characteristics of HPS6-deficient mouse endothelial cells. We observed similar morphological changes of WPBs in HUVECs after the knockdown of ATP6V0D1 (a subunit of v-ATPase). Furthermore, we found that HPS6 interacted with ATP6V0D1, suggesting that HPS6 transports ATP6V0D1 to the WPB limiting membrane for the assembly of the v-ATPase complex to maintain its acidic luminal pH, which is critical for the formation of vWF tubules during WPB maturation. In conclusion, HPS6 likely regulates the biogenesis of WPBs by participating in the trafficking of v-ATPase to the WPB membrane.